Mathématiques
FannyDrew
8

bonjour equation -2x+5=-2-9x 4x-7=-7+4x 2(x-3=5(-x+1) -3(x+5)=1-2(x+1) x-(7x-2)=5(2-x) 1-(5-2x)=3-(2x-5)

+0
(1) Réponses
Lolita2503

-2x + 5 = -9x − 2 -2x + 9x = -2 − 5 7x = -7 x = -1-----------------------4x − 7 = 4x − 7 4x − 4x = -7 + 7 0x = 0-----------------------2(x-3)=5(-x+1) 2x − 6 = -5x  + 5 2x  + 5x = 5 + 6 7x = 11 x = 11/7--------------------------3(x+5)=1-2(x+1) -3x -15 = 1 -(2x+2) -3x - 15 = 1 - 2x - 2 -3x - 15 = -2x -1 -3x + 2x = +15 -1 x = -14----------------------------x-(7x-2)=5(2-x) -6x +2 = 10 - 5x -6x+5x = 10 - 2 -1x = 8 x = -8---------------------------1-(5-2x)=3-(2x-5) 2x − 4 = -2x + 8 2x + 2x = 8 + 4 4x = 12 x = 12/4 x= 3

Ajouter une réponse